Postactivation potentiation enhances swim performance in collegiate swimmers - Hancock, A. P.; Sparks, K. E.; Kullman, E. L. (The Journal of Strength and Conditioning Research, 2015)
This study examined postactivation potentiation (PAP) and its effect on performance during sprint swimming. After maximal muscular contraction, the muscles are in both a potentiated and fatigued state. However, fatigue dissipates faster than potentiation, creating a window of opportunity for possible performance enhancement. We observed 30 collegiate swimmers (15 men and 15 women) performing 2 swim trials in a randomized order. The control trial involved a standard swim warm-up, followed by a 6-minute rest and by a maximal 100-m freestyle swim effort. The PAP trial involved the same protocol; however, a PAP loading protocol involved the subjects completing 4 maximal 10-m swims at a 1-minute interval while attached to a resistive power rack and was completed before the 6-minute rest. Fifty-meter splits and blood lactates were also analyzed. There was a significant improvement in 100-m freestyle swim time (0.54 seconds) for the PAP trial vs. the control trial (p = 0.029). Both men and women improved during the PAP trial compared with the control trial, and there was no significant gender interaction. We conclude that PAP substantially enhances 100-m freestyle performance in collegiate swimmers and presents a valid technique for competitive performance enhancement.